2012
DOI: 10.1007/s11605-012-2002-7
|View full text |Cite
|
Sign up to set email alerts
|

Parenchyma-Sparing Resections for Pancreatic Neuroendocrine Tumors

Abstract: In selected patients, with small and low-grade tumors, PSP are associated with excellent overall and recurrence-free survivals. These procedures are associated with an increased postoperative morbidity but an excellent postoperative pancreatic function. Therefore, they should be considered as a valid therapeutic option in selected well-differentiated pancreatic neuroendocrine tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
89
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(98 citation statements)
references
References 56 publications
4
89
0
2
Order By: Relevance
“…Although long-term morbidity was not accessed in our study, previous studies have shown enucleation superior to formal resection in terms of diabetes and exocrine pancreas insufficiency. 12 Enucleated tumors were all WHO 2010 grade 1 or 2, with size between 10 and 23 mm, and none of them recurred or caused mortality. These results indicate that enucleation is a viable option in these patients with acceptable morbidity.…”
Section: Discussionmentioning
confidence: 97%
“…Although long-term morbidity was not accessed in our study, previous studies have shown enucleation superior to formal resection in terms of diabetes and exocrine pancreas insufficiency. 12 Enucleated tumors were all WHO 2010 grade 1 or 2, with size between 10 and 23 mm, and none of them recurred or caused mortality. These results indicate that enucleation is a viable option in these patients with acceptable morbidity.…”
Section: Discussionmentioning
confidence: 97%
“…For our patient, the options available for treating the pancreatic lesion were limited due to its size, but, given the proximity to the adrenal lesion, the possibility of a resection was taken into account. Pancreatic enuclation is the gold standard for lesions located close to the surface of the head or body of the pancreas and far (>2 mm) away from the Wirsung duct, and when the lesions are multiple (13). Song et al (15) limited the laparoscopic approach to superficial and anterior lesions that are located in the left side of the superior mesenteric vein, similarly to the present case study.…”
Section: Discussionmentioning
confidence: 61%
“…The final anatomical limitation for enucleation is the distance between the tumors and the main pancreatic duct, which should be, even if not yet evidence-based, >2 mm (13). Indeed, one of the major risks associated with enucleating large lesions is a major pancreatic duct injury, leading to high output pancreatic fistula, as occurred in the present case study.…”
Section: Discussionmentioning
confidence: 69%
“…A cushion is placed under the tips of the scapulas to enhance exposure, especially in a corpulent patient. The incision can be a supraumbilical midline incision (1) or a bilateral subcostal incision (2). A short transverse incision centered on the lesion is also possible (3 or 4).…”
Section: Patient Position and Approachmentioning
confidence: 99%
“…• benign or at low risk for malignancy [2] (non-secreting endocrine or insulin-secreting tumors, serous or mucinous cystadenomas and more infrequently, intraductal papillary mucinous neoplasms limited to one branch duct; • located ideally at least 2 mm from the main pancreatic duct [2]; • principally when these tumors are superficial [3]; • or located in the head or body of the pancreas (because caudal lesions can be treated by a short distal pancreatectomy) [3]; • and usually less than 4 cm in diameter [4]. Nevertheless, caution is warranted for endocrine tumors whose large diameter is between 2 and 4 cm where the risk of cancer exceeds 10% [4].…”
Section: Introductionmentioning
confidence: 99%